FINDING ROOTS OF SYSTEM OF NON LINEAR EQUATIONS USING SPIRAL DYNAMICS INSPIRED OPTIMIZATION - VIDYA UTAMI, ANISA
Global optimization problem can be solved by several methods. Each method has its own strategies and parameters, that the effectiveness and the accuracy on finding the global optimum value can be different for each method. Some of the optimization methods cannot avoid the local optimum, some else need the derivative of function. Those methods has its strengths and weaknesses. Finding roots of systems of non linear equations inside bounded domain is not easy, moreover it can be very difficult in some cases. Metaheuristics method is an effective method for finding roots of systems of non linear equations inside bounded domain. Writer proposed a new metaheuristics method from Kenichi Tamura and Keiichiro Yasuda, year 2011, the Spiral Dynamics Inspired Optimization algorithm. Finding roots of systems of non linear equations can be done with solving optimization problem that constructed from the non linear equations system. For finding all roots on systems of non linear equations inside bounded domain, we use Grouping Technique. The search processing with that technique is not only in one location of the roots, but it search on several locations. Beside that, this final project will explain how to use the Spiral Dynamics Inspired Optimization algorithm equipped with Grouping Technique for finding not only the Real roots, but also the Complex roots.